The potential of nanomedicine therapies to treat neovascular disease in the retina - Farjo, Krysten M; Ma, Jian-xing (Vascular Cell, 2010)
Abstract Neovascular disease in the retina is the leading cause of blindness in all age groups. Thus, there is a great need to develop effective therapeutic agents to inhibit and prevent neovascularization in the retina. Over the past decade, anti-VEGF therapeutic agents have entered the clinic for the treatment of neovascular retinal disease, and these agents have been effective for slowing and preventing the progression of neovascularization. However, the therapeutic benefits of anti-VEGF therapy can be diminished by the need for prolonged treatment regimens of repeated intravitreal injections, which can lead to complications such as endophthalmitis, retinal tears, and retinal detachment. Recent advances in nanoparticle-based drug delivery systems offer the opportunity to improve bioactivity and prolong bioavailability of drugs in the retina to reduce the risks associated with treating neovascular disease. This article reviews recent advances in the development of nanoparticle-based drug delivery systems which could be utilized to improve the treatment of neovascular disease in the retina.